ANALYSIS OF MEDAN CITY STRUCTURE BASED ON DISTRICT / CITY SPATIAL PLAN - Rini Kustiah Rahmadiana (Bulletin of Engineering Science, Technology and Industry, 2024)
This research aims to analyze and determine the suitability of determining the Regional Spatial Plan (RTRW) for Medan City for 2022-2042 in several sub-districts, as the center of economic growth in Medan City. Also to determine the level of geographic distribution of the availability of public facilities in each sub-district in Medan City. The research method used is a qualitative research method with a descriptive approach. The qualitative-descriptive method is a research procedure that produces descriptive data in the form of written or spoken words and observable behavior. The results of the research show that there are several sub-districts that do not comply with the Medan City RTRW projections for 2022 - 2042 in terms of urban spatial structure and there are also sub-districts whose designation is appropriate. This can be seen from the results of scalogram analysis and regional gravity analysis.